Application Of Fuzzy Logic In The Measurement System Of Student Satisfaction Level Towards Lecturers Based On The Fuzzy Infrence Analysis Of The Mamdani, Sugeno And Tsukatomo Method System - Yuda Perwira; Risa Kartika Lubis (Sean Institute, 2021)
Service to students is an important aspect for the comfort of students at universities in undergoing study process, one of the services that need to be considered is student satisfaction with lecturers, especially in private universities, student satisfaction with lecturers is very influential because it can have an impact on the absorption of knowledge provided to achievement. for students, it is necessary for the right method to measure the level of student satisfaction with lecturers, the purpose of this study is to perform a comparative analysis of the fuzzy Inference system of the Mamdani, Sugeno, and Tsukamoto methods to be able to measure the level of student satisfaction with lecturers accurately and with the right method, The stages of this research method are data collection from STMIK Pelita Nusantara, data identification as the basis for fuzzification formation, fuzzy inference system process with Mamdani, Sugeno, and Tsukamoto methods, then analysis of the three t-methods is carried out. This is to select which method is the most accurate, then carry out system development and system implementation. The results obtained in this study are the Fuzzy Inference System has been successfully created and can be applied to this research, and from the comparison of the 3 methods, it is known for level measurement research. student satisfaction with lecturers, the best method is the Sugeno method, in addition to its high accuracy, determining the constants to be values that match the criteria for the assessment range and also the calculations are not so complicated.